2010
DOI: 10.3357/asem.2594.2010
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Simulated Flight Path Control at +3 G<SUB>z</SUB> in a Human Centrifuge

Abstract: We conclude that force exaggeration in +3 Gz may impair flight stability during simulated jet maneuvers in naïve subjects, most likely as a consequence of vestibular stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Studies have shown that states of high G forces cause increases in isometric forces Sand et al 2003;Girgenrath et al 2005;) but have no affect on the displacement of movements of the control stick in a fighter jet. Guardiera et al (2010) examined the ability of pilots to maintain flight path stability in a +3g centrifuge. They found that pilots had over exaggerated forces, but no difference in the displacement of movements during increased gravity, which potentially affected their ability to perform stable maneuvers at high G forces.…”
Section: 31: Altered Gravitymentioning
confidence: 99%
“…Studies have shown that states of high G forces cause increases in isometric forces Sand et al 2003;Girgenrath et al 2005;) but have no affect on the displacement of movements of the control stick in a fighter jet. Guardiera et al (2010) examined the ability of pilots to maintain flight path stability in a +3g centrifuge. They found that pilots had over exaggerated forces, but no difference in the displacement of movements during increased gravity, which potentially affected their ability to perform stable maneuvers at high G forces.…”
Section: 31: Altered Gravitymentioning
confidence: 99%
“…As in our other study (9), subjects sat wearing an anti-G suit in the fl ight simulator of the GAF Institute of Aviation Medicine in Königsbrück. The cabin of this 9-m centrifuge is equipped with a reproduction of the Eurofi ghter cockpit, including control panels and a realistic view of a pilot's surroundings.…”
Section: Methodsmentioning
confidence: 99%
“…Due to this combination of forces and displacements used in regular sticks, a manual response exaggeration during phases of 1 G z turn out to be plausible as well and have indeed been observed. We documented a signifi cant, albeit less pronounced, exaggeration of responses ( 1 13%) in 1 3 G z even with the reproduction of the Eurofi ghter 2000 stick, which responds to a combination of force and displacement (9).…”
mentioning
confidence: 96%
See 2 more Smart Citations